The relationships between brain structural changes and perceived loneliness in older adults suffering from late‐life depression - Sin, Emily L.L.; Liu, Ho‐Ling; Lee, Shwu‐Hua; Huang, Chih‐Mao; Wai, Yau‐Yau; Chen, Yao‐Liang; Chan, Chetwyn C.H.; Lin, Chemin; Lee, Tatia M.C. (International journal of geriatric psychiatry, 2018)
Objective Late‐life depression is a significant health risk factor for older adults, part of which is perceived loneliness. In this voxel‐based morphometry study, we examined the relationships between perceived loneliness and depression recurrence. Methods Fifty‐two older adults were recruited, and they were split into 3 groups: single episode, multiple episodes, or normal control groups, according to their clinical histories. Results This result suggests the level of functioning regarding the reward system may be negatively related to the number of depressive episodes. Taken together, the findings of this study offer important insight into the neural underpinnings of the course and chronicity of late‐life depression.